Formalization of the reengineering problem of ground-based environmental monitoring networks topological structures - Beskorovainyi, V.; Semenets, V. (My University, 2021)
Changes in operating conditions or monitoring tools reduces the effectiveness of existing options for implementing networks and requires their reengineering. To ensure the effectiveness of design solutions, it is proposed to jointly solve the problems of structural, topological, parametric and technological optimization of system networks in terms of a variety of indicators. The basic formulation of the problem of reengineering of the topological structures of centralized three-level ground networks has been determined, for which a set of feasible solutions and estimates of indicators of costs, efficiency, reliability and survivability are formalized. Taking into account the fact that the cardinalities of the sets of admissible functioning technologies, parameters of elements and connections of networks are insignificant, the main difficulties are in solving problems of optimizing their topological structures. Such problems are solved with a variety of functional and cost indicators, taking into account numerous restrictions. The proposed universal functions for scalar estimation of options more accurately describe the preferences of the decision-maker and reduce the time complexity of the estimation procedures. Mathematical relationships were obtained to assess options for building centralized three-level networks in terms of costs, efficiency, reliability and survivability. Their use makes it possible to carry out scalar evaluations of alternative options in automatic mode. The proposed options evaluation functions more accurately describe the benefits of the design decision maker and allow reducing the time complexity of the evaluation procedures
Keywords: Environmental monitoring network; structure; topology; reengineering; multi criteria optimization